Jakość usług sportowo-rekreacyjnych = The quality of sport-recreation services - Agnieszka Widawska-Stanisz (Kazimierz Wielki University, 2015)
Widawska-Stanisz Agnieszka. Jakość usług sportowo-rekreacyjnych = The quality of sport-recreation services. Journal of Education, Health and Sport. 2015;5(11):492-503. eISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.35688 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2811%29%3A492-503 http://pbn.nauka.gov.pl/works/684739 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011-2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Original Text published © The Author (s) 2015. Widawska-Stanisz Agnieszka. Jakość usług sportowo-rekreacyjnych. Quality in Sport. 2015;1(1):66-76. eISSN 2450-3118. http://ojs.ukw.edu.pl/index.php/QiS/article/view/QUALITY%20IN%20SPORT%201%20%281%29%202015%2C%20s.%2066-76   The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport (null) 2391-8306 7 © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland. Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.11.2015. Revised 20.11.2015. Accepted: 30.11.2015.   Agnieszka Widawska-Stanisz Wydział Zarządzania, Politechnika Częstochowska   Jakość usług sportowo-rekreacyjnych The quality of sport-recreation services       Streszczenie W artykule scharakteryzowano usługi sportowo-rekreacyjne i ich jakość. Przedstawiono najważniejsze czynniki determinujące wysoką jakość świadczonych usług oraz znaczenie standardów jakości w procesie świadczenia usług sportowo-rekreacyjnych. Przedstawiono wyniki badania przeprowadzonego wśród mieszkańców województwa śląskiego na temat oferty przedsiębiorstw sportowo-rekreacyjnych i jakości świadczonych przez nie usług.   Słowa kluczowe: jakość usług, usługi sportowo-rekreacyjne, nabywca.     Abstract There is a description of sport- recreation services and their quality presented in this article. The most important factors determining the high quality of providing services and the meaning of quality standards in the process of providing sport- recreation services are shown. There are some research results conducted among residents of Silesia province on the offers of sport - recreation companies and the qualities of their services.       Key words: the quality of services, sport- recreation services, purchaser.